Mathematics Teaching Materials Based on the Ethnomathematics of Shiva Temple by Applying the "Tri-N" Teaching - Davi Apriandi; Annis Deshinta Ayuningtyas (AL-ISHLAH: Jurnal Pendidikan, 2022)
Education as a process of cultural transformation is a cultural inheritance from one generation to the next. Ethnomathematics can bridge the gap between culture and learning mathematics. One of the cultural elements to be integrated into mathematics learning is to use one of the cultural sites in Yogyakarta, namely the Shiva Temple. This is done to increase students' interest in culture through learning mathematics. Various cultural elements that can be studied at the Shiva Temple include buildings, architecture, ornaments, statues, etc. Besides being based on the ethnomathematics of Shiva Temple, the approach that can be used is Tamansiswa's teachings, namely Niteni, Nirokke, and Nambahi (3N). To facilitate students in learning the material for building flat sides, it is necessary to have interesting, fun, and culturally related teaching materials. Therefore, this study aims to describe the ethnomathematics-based teaching materials of Shiva Temple by applying the teachings of Niteni, Nirokke, Nambahi. This research is a qualitative descriptive study. The data were obtained through direct observation, interviews with the Prambanan temple tourism park manager, documentation, and literature study. The results obtained are the design of teaching materials that contain a summary of the material and practice questions regarding the shape of the flat side space in which there are many pictures of ornaments, and statues found in the Shiva Temple and written with the application of the teachings of Niteni, Nirokke, Nambahi.